2010
DOI: 10.1007/s11136-010-9774-6
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional validation study of EQ-5D among the Malaysian adult population

Abstract: This study has demonstrated acceptable construct validity of the EQ-5D among the Malaysian population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 20 publications
2
45
1
Order By: Relevance
“…A large ceiling effect (a large proportion of the population tending to report good health, which here refers to reporting no problems in any EQ-5D dimensions) as found in our study (87%) has also been observed in other studies including Chinese populations, in China (Wang et al, 2005), as well as in US (Fu & Kattan, 2006;Lubetkin et al, 2005) and Canada (Leung et al, 2007). This was also the case in a study in Japan (Tsuchiya et al, 2002) and in Malaysia (Shafie et al, 2010).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A large ceiling effect (a large proportion of the population tending to report good health, which here refers to reporting no problems in any EQ-5D dimensions) as found in our study (87%) has also been observed in other studies including Chinese populations, in China (Wang et al, 2005), as well as in US (Fu & Kattan, 2006;Lubetkin et al, 2005) and Canada (Leung et al, 2007). This was also the case in a study in Japan (Tsuchiya et al, 2002) and in Malaysia (Shafie et al, 2010).…”
Section: Discussionsupporting
confidence: 89%
“…EQ-5D population health studies have been performed mostly in Europe (Burström, Johannesson, & Diderichsen, 2001;Kind, Dolan, Gudex, & Williams, 1998;König et al, 2009;Sorensen, Davidsen, Gudex, Pedersen, & Bronnum-Hansen, 2009;Szende & Williams, 2004), USA (Fryback, Dunham, Palta, Hanmer, Buechner, & Cherepanov, 2007;Lubetkin, Jia, Franks, & Gold, 2005;Luo, Johnson, Shaw, Feeny, & Coons, 2005), Canada (Leung, Luo, So, & Quan, 2007) and Asia (Kil, Lee, Yun, An, & Jo, 2008;Shafie, Hassali, & Liau, 2010;Ting, Tarn, Ching, Liou, Shaw, & Chiou, 2007;Tsuchiya, & et al, 2002), including China (Sun et al, 2010;Wang, David, Mullahy, & Mullahy, 2005). Studies among other Chinese populations have also been performed in Singapore (Luo, Chew, Fong, Koh, Ng, & Yoon, 2003), the USA (Lubetkin et al, 2007;Luo et al, 2005) and Canada (Leung et al, 2007).…”
mentioning
confidence: 99%
“…Evidence also showed that GDP per capita and healthcare expenditure is correlated most with the EQ VAS score. 19 However, Shafie et al 12 showed that the health status was positively associated with education, but had no significant association with income. The study has some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…8 The EQ-5D instrument has widely been used in North America, Europe, and a few low-and middle-income countries in Asia and Africa. [9][10][11][12][13][14][15] In Bangladesh, a few studies have used the EQ-5D instrument for measuring health status. This instrument was employed by Saleh et al 16 to measure the health-related quality of life among patients with type 2 diabetes and used Shaheen and Lindholm 17 to measure the quality of life among pregnant women with chronic energy deficiency in rural Bangladesh.…”
Section: Key Messagesmentioning
confidence: 99%
“…A higher score indicates better functioning, less pain or greater well-being. Shafie et al (2011) reported a moderately positive convergent validity between PCS and MCS with EuroQoL-5 dimensions in a study among 596 Malaysian adults.…”
Section: Twelve-item Short Form (Sf-12)mentioning
confidence: 98%